2016
DOI: 10.1093/ije/dyw146
|View full text |Cite
|
Sign up to set email alerts
|

Childhood socioeconomic disadvantage is associated with lower mortality in older Japanese men: the JAGES cohort study

Abstract: Background: Childhood socioeconomic disadvantage has been previously linked to increased mortality risk in adulthood. However, most previous studies have focused on middle-aged adults in Western contexts. Here, we sought to examine the association between childhood socioeconomic status (SES) and mortality among healthy older Japanese adults.Methods: We conducted a 3-year follow-up of participants in the Japan Gerontological Evaluation Study (JAGES), a population-based cohort of 65- to 103-year-old Japanese adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…Consistent with our study, a previous Japanese study showed that lower childhood SES was associated with lower mortality later in life among males in the oldest age group who experienced poverty in post‐World War II, compared with a younger age group. Although the oldest age group experienced calorie restrictions in early life due to harvest failure and a poorly operated food distribution system, this generation survived adverse childhood experiences to become a healthy older population . The proposed mechanisms should be carefully examined in the future.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Consistent with our study, a previous Japanese study showed that lower childhood SES was associated with lower mortality later in life among males in the oldest age group who experienced poverty in post‐World War II, compared with a younger age group. Although the oldest age group experienced calorie restrictions in early life due to harvest failure and a poorly operated food distribution system, this generation survived adverse childhood experiences to become a healthy older population . The proposed mechanisms should be carefully examined in the future.…”
Section: Discussionsupporting
confidence: 58%
“…Although the oldest age group experienced calorie restrictions in early life due to harvest failure and a poorly operated food distribution system, this generation survived adverse childhood experiences to become a healthy older population. 41 The proposed mechanisms should be carefully examined in the future. In contrast, our results with no statistical significance in men supported some previous studies.…”
Section: Income and The Risk Of Acquiring Dementiamentioning
confidence: 99%
“…Cohort data from two on-going prospective cohort studies, the English Longitudinal Study of Ageing (ELSA) [8, 9] and the Japan Gerontological Evaluation Study (JAGES) Project [10, 11], were used in this analysis. ELSA targets independent-living older adults in England aged 50 years or older and the first wave was conducted between 2002 and 2003.…”
Section: Methodsmentioning
confidence: 99%
“…The association between childhood socioeconomic circumstances and adult health has been extensively examined for high-income countries (Claussen et al, 2003;Galobardes et al, 2008;Kestila et al, 2009;Khang, 2006;Kuh et al, 2002;Lawlor et al, 2002;Marin et al, 2008;McKenzie et al, 2011;Mishra et al, 2013;Parsons et al, 1999;Poulton et al, 2002;Power et al, 2007;Power et al, 2005;Senese et al, 2009;Singh-Manoux et al, 2004;Tani et al, 2016;Tiffin et al, 2005;Tiikkaja et al, 2009;Turrell et al, 2007;Atheendar S. Venkataramani et al, 2016a;A. S. Venkataramani et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from earlier studies in Japan suggests that, contrary to the findings for western countries, childhood socioeconomic disadvantage may be associated with lower mortality among older men. (Tani et al, 2016) The authors interpret this paradoxical result in several ways: selective survival, preventive effects of childhood physical training, and the effect of post-war calorie restrictions on chronic diseases.…”
Section: Introductionmentioning
confidence: 99%